Evaluating near infrared hyperspectral imaging as a complimentary rapid screening tool for food microbiology - Mapling, Celeste Nadine (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2021.